Motivasi Perempuan Bergabung Komunitas Suporter Sepakbola - Fahri, Achmad Syakur; Akhiruyanto, Andry; Willianto, Septian; Pambudi, Yudhi Teguh; Agus, Herdiansyah; Sutarza, Encep Farlan (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2023)
Football is an entertainment for many people, not only for men but also for women. Although there are many problems related to comfort, harassment, security and even supporters' riots that have claimed lives, it is not a reason for women to build a community of football supporters. The focus of this study is to determine the motivation of women to join the supporters group community in terms of Maslow's motivation theory, namely (1) physiological needs, (2) security needs, (3) social needs, (4) need for appreciation and (5) self-actualization. Qualitative methods were used in this study with data triangulation in the form of observation, interviews and documentation conducted for 5 (five) months. The research population was members of the PSIS Semarang football supporter community, with a sample of 33 female supporter members, as evidenced by KTA (membership card). Interviews were conducted with 33 (thirty-three), including 16 (sixteen) main informants representing all districts in Semarang City and 16 (sixteen) supporting informants, namely colleagues of the main informants and 1 (one) person, namely the head of the community. Observations were made during the match, after the match, before the match and during community activities, and documentation was obtained through documentary evidence provided by informants and community leaders, and then the data was coded and triangulated into narrative paragraphs. The results showed that of the 16 (sixteen) main informants, there were 4 (four) high school students, 4 (four) students and 8 (eight) workers who had an average age of 21 years. Based on Maslow's motivation theory, the highest and most dominant need for them to join the supporter's group is because of social needs and the least fulfilled need is physiological needs. The needs for security, self-actualization and appreciation are fulfilled but lower than social needs. Their main goal is to join the supporters group because they feel safer and appreciated, get recognition and actively contribute to activities outside the stadium, such as social and humanitarian services. The conclusion that can be drawn from this research is that the strongest motivation for the PSIS Semarang female supporters group to join the supporter group is the social need to express their love for the Semarang PSIS team, then the need for security, appreciation and self-actualization they still get by joining the supporter's group but it is not the main need. Meanwhile, physiological needs are the least fulfilled needs. Recommendations for other researchers based on this study are to find out and prove the benefits of joining women in football supporter groups. On the other hand, considering the growing football industry, further research needs to be done regarding the role of women, especially supporters, in the development of football in Indonesia.